The Role of Technical Skills as a Mediator in the Effect of Training and WorkEnvironment on Employee Productivity in the Mining Industry - Vera Anitra; Risma Wulan Dari; Fredi Handoko (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the mediating role of technical skills in the relationship between training and work environment on employee productivity within several mining companies in Indonesia. Using a quantitative approach and Partial Least Square Structural Equation Modeling (PLS-SEM), data were obtained from 150 respondents selected through purposive sampling. The sample size was determined based on Slovin's formula assuming a population of 3,000 mining workers with a 7% margin of error, and by referring to Hair et al. (2017), which recommends a minimum of 10 times the number of indicators in the largest construct for PLS-SEM. The results indicate that both training and work environment have positive and significant effects on technical skills, and technical skills significantly influence employee productivity. Additionally, training and work environment have a direct effect on productivity, which is partially mediated by technical skills. All constructs in the model meet the requirements for convergent validity and internal reliability. These findings emphasize the importance of continuous investment in training programs and the creation of a supportive work environment to enhance technical competencies and employee productivity in the mining sector.